The Language Function in the Discourse Produced by Traditional Medicine Sellers - Rahmatika Ananda; Hamzah Hamzah (Universitas Negeri Padang, 2019)
AbstractThe purpose of this research is to investigate the language function from the discourse produced by traditional medicine sellers. The method used in this research is descriptive method. The data of this research were obtained from the discourse produced by five medicine sellers in different area. The data were analyzed by using Geoffery Leech (1974) theory. The finding divided into three types, they were informative, directive, and phatic function. In informative function also found four type of informative, they were giving opinion, advice, making announcement, and admonish. In directive function was found two types, they were command and request. Last was phatic function. Most of conversations had similar types of language function. However, findings showed that there were some types of language function were not found in each section of conversation produced by traditional medicine sellers. The language functions used by traditional medicine sellers were in line with the purpose of marketing, they were to inform, persuade, and remind the costumer about the product that sold.